A Marxist Mosaic : Selected Writings 1968-2022 - Banaji, Jairus, (Historical Materialism Book Series ;, 2024)
Historical materialism as Marx understood this was always an integrated conception or field of research, not one divided into separate disciplines. The essays gathered in this volume are a remarkable example of how this works across a wide range